Towards bottom-up nanopatterning of Prussian blue analogues - Trannoy, Virgile; Faustini, Marco; Grosso, David; Mazerat, Sandra; Brisset, François; Dazzi, Alexandre; Bleuzen, Anne (Beilstein Journal of Nanotechnology, 2014)
Ordered nanoperforated TiO2 monolayers fabricated through sol–gel chemistry were used to grow isolated particles of Prussian blue analogues (PBA). The elaboration of the TiO2/CoFe PBA nanocomposites involves five steps. The samples were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), infrared spectroscopy and X-ray photoelectron spectroscopy (XPS) all along the synthesis process. Selected physico-chemical parameters have been varied in order to determine the key steps of the synthesis process and to optimize it. This study is an important step towards the full control of the fabrication process.
Keywords: nanopatterning; nanoperforated oxide monolayer; Prussian blue analogues

(untitled) - Entley, W. R.; Girolami, G. S. (Science, 1995)

(untitled) - Ferlay, S.; Mallah, T.; Ouahes, R.; Veillet, P.; Verdaguer, M. (Nature, 1995)

(untitled) - Sato, O.; Iyoda, T.; Fujishima, A.; Hashimoto, K. (Science, 1996)

(untitled) - Bleuzen, A.; Lomenech, C.; Escax, V.; Villain, F.; Varret, F.; Cartier dit Moulin, C.; Verdaguer, M. (J. Am. Chem. Soc., 2000)

(untitled) - Li, D.; Clérac, R.; Roubeau, O.; Harté, E.; Mathonière, C.; Le Bris, R.; Holmes, S. M. (J. Am. Chem. Soc., 2008)

(untitled) - Mercurol, J.; Li, Y.; Pardo, E.; Risset, O.; Seuleiman, M.; Rousselière, H.; Lescouëzec, R.; Julve, M. (Chem. Commun., 2010)

(untitled) - Hoshino, N.; Iijima, F.; Newton, G. N.; Yoshida, N.; Shiga, T.; Nojiri, H.; Nakao, A.; Kumai, R.; Murakami, Y.; Oshio, H. (Nat. Chem., 2012)

(untitled) - Cafun, J.-D.; Cartier dit Moulin, C.; Fornasieri, G.; Arrio, M.-A.; Briois, V.; Bleuzen, A. (New J. Chem., 2011)

Inorganic Chemistry - Ludi, A.; Güdel, H. (Structural chemistry of polynuclear transition metal cyanides, 1973)

Sol-Gel Science: The Physics and Chemistry of Sol-Gel Processing - Brinker, C. J.; Scherer, G. W. (Gulf Professional Publishing, 1990)

(untitled) - Kresge, C. T.; Leonowicz, M. E.; Roth, W. J.; Vartuli, J. C.; Beck, J. S. (Nature, 1992)

(untitled) - Fisher, A.; Kuemmel, M.; Järn, M.; Linden, M.; Boissière, C.; Nicole, L.; Sanchez, C.; Grosso, D. (Small, 2006)

(untitled) - Schulze, C.; Faustini, M.; Lee, J.; Schletter, H.; Lutz, M. U.; Krone, P.; Gass, M.; Sader, K.; Bleloch, A. L.; Hietschold, M.; Fuger, M.; Suess, D.; et al. (Nanotechnology, 2010)

(untitled) - Allouche, J.; Lantiat, D.; Kuemmel, M.; Faustini, M.; Laberty, C.; Chaneac, C.; Tronc, E.; Boissiere, C.; Nicole, L.; Sanchez, C.; Grosso, D. (J. Sol-Gel Sci. Technol., 2010)

(untitled) - Lepoutre, S.; Grosso, D.; Sanchez, C.; Fornasieri, G.; Rivière, E.; Bleuzen, A. (Adv. Mater., 2010)

(untitled) - Volatron, F.; Heurtaux, D.; Catala, L.; Mathonière, C.; Gloter, A.; Stéphan, O.; Repetto, D.; Clemente-León, M.; Coronado, E.; Mallah, T. (Chem. Commun., 2011)

(untitled) - Pajerowski, D. M.; Gardner, J. E.; Frye, F. A.; Andrus, M. J.; Dumont, M. F.; Knowles, E. S.; Meisel, M. W.; Talham, D. R. (Chem. Mater., 2011)

(untitled) - Cobo, S.; Molnár, G.; Carcenac, F.; Szilágyi, P. Á.; Salmon, L.; Vieu, C.; Bousseksou, A. (J. Nanosci. Nanotechnol., 2010)

(untitled) - Kuemmel, M.; Allouche, J.; Nicole, L.; Boissière, C.; Laberty, C.; Amenitsch, H.; Sanchez, C.; Grosso, D. (Chem. Mater., 2007)

(untitled) - Mutin, P. H.; Guerrero, G.; Vioux, A. (C. R. Chim., 2003)

(untitled) - Guerrero, G.; Mutin, P. H.; Vioux, A. (Chem. Mater., 2001)

(untitled) - Sanchez, C.; Boissière, C.; Grosso, D.; Laberty, C.; Nicole, L. (Chem. Mater., 2008)

(untitled) - Faustini, M.; Drisko, G. L.; Boissiere, C.; Grosso, D. (Scr. Mater., 2014)

(untitled) - Faustini, M.; Boissière, C.; Nicole, L.; Grosso, D. (Chem. Mater., 2014)

(untitled) - Shon, Y.-S.; Gross, S. M.; Dawson, B.; Porter, M.; Murray, R. W. (Langmuir, 2000)

(untitled) - Pasquinet, E.; Bouvier, C.; Thery-Merland, F.; Hairault, L.; Lebret, B.; Méthivier, C.; Pradier, C. M. (J. Colloid Interface Sci., 2004)

(untitled) - Tricard, S.; Raza, Y.; Mazerat, S.; Aissou, K.; Baron, T.; Mallah, T. (Dalton Trans., 2013)

(untitled) - Tricard, S.; Fabrice, C.; Mallah, T. (Dalton Trans., 2013)

Infrared and Raman spectra of inorganic and coordination compounds - Nakamoto, K. (Wiley-Interscience, 1986)

(untitled) - Bonhommeau, S.; Pontius, N.; Cobo, S.; Salmon, L.; de Groot, F. M. F.; Molnár, G.; Bousseksou, A.; Durr, H. A.; Eberhardt, W. (Phys. Chem. Chem. Phys., 2008)